2018
DOI: 10.1007/s12105-018-0926-2
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Surgical Approach of the Ear and Temporal Bone

Abstract: The temporal bone is one of the more complex structures at the skull base that houses the hearing and vestibular organs, numerous nerves, and vessels. A host of inflammatory and neoplastic processes can occur within the temporal bone that often necessitate permanent and frozen section pathologic examination. A number of simple to complex surgical procedures are used to manage temporal bone pathology. This chapter will provide a brief overview of normal temporal bone anatomy, common surgical approaches, normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…To avoid iatrogenic injury to the adjacent structures, the MA must be open superiorly toward TT. The tympano-mastoid suture at the posterior wall of the MA is surface marking of the course of the vertical portion of the facial nerve (FN) [9,16,18]. Peris-Celda et al reported that the parietal notch corresponds to the posterior petrosal point and the SS (the transverse-SS junction) in 66 and 34% of the cases, respectively [9].…”
Section: Surgical Landmarks and Ossification Of The Mastoid Portionmentioning
confidence: 99%
See 4 more Smart Citations
“…To avoid iatrogenic injury to the adjacent structures, the MA must be open superiorly toward TT. The tympano-mastoid suture at the posterior wall of the MA is surface marking of the course of the vertical portion of the facial nerve (FN) [9,16,18]. Peris-Celda et al reported that the parietal notch corresponds to the posterior petrosal point and the SS (the transverse-SS junction) in 66 and 34% of the cases, respectively [9].…”
Section: Surgical Landmarks and Ossification Of The Mastoid Portionmentioning
confidence: 99%
“…Laterally, external surface is bounded by the cartilaginous part of the EAC which extends from the auricle to the tympanic membrane. The EAC is an S-shaped tube, about 2.5 cm in long, that is composed of the lateral third cartilaginous part and the medial two-thirds osseous part [14,15,18]. The tympanic part constructs the anterior wall and floor and the lower part of posterior wall of the EAM, whereas the squamous part forms the superior and upper part of the posterior wall of it (Figure 1).…”
Section: Borders and Surfaces Of The Tympanic Portionmentioning
confidence: 99%
See 3 more Smart Citations